A Pediatric Cervical Spine Clearance Guideline Leads to Fewer Unnecessary Computed Tomography Scans and Decreased Radiation Exposure. Issue 5 (30th May 2023) - Douglas, Geoffrey P.; McNickle, Allison G.; Jones, Stephanie A.; Dugan, Mark C.; Kuhls, Deborah A.; Fraser, Douglas R.; Chestovich, Paul J.
Abstract : Objectives: Physical examination and computed tomography (CT) are useful to rule out cervical spine injury (CSI). Computed tomography scans increase lifetime cancer risk in children from radiation exposure. Most CSI in children occur between the occiput and C4. We developed a cervical spine (C-spine) clearance guideline to reduce unnecessary CTs and radiation exposure in pediatric trauma patients. Methods: A pediatric C-spine clearance guideline was implemented in September 2018 at our Level 2 Pediatric Trauma Center. Guidance included CT of C1 to C4 to scan only high-yield regions versus the entire C-spine and decrease radiation dose. A retrospective cohort study was conducted comparing preguideline and postguideline of all pediatric trauma patients younger than 8 years screened for CSI from July 2017 to December 2020. Primary endpoints included the following: number of full C-spine and C1 to C4 CT scans and radiation dose. Secondary endpoints were CSI rate and missed CSI. Results were compared using χ 2 and Wilcoxon rank-sum test with P < 0.05 significant. Results: The review identified 726 patients: 273 preguideline and 453 postguideline. A similar rate of total C-spine CTs were done in both groups (23.1% vs 23.4%, P = 0.92). Full C-spine CTs were more common preguideline (22.7% vs 11.9%, P < 0.001), whereas C1 to C4 CT scans were more common post-guideline (11.5% vs 0.4%, P < 0.001). Magnetic resonance imaging utilization and CSIs identified were similar in both groups. The average radiation dose was lower postguideline (114 vs 265 mGy·cm −1 ; P < 0.001). There were no missed CSI. Conclusions: A pediatric C-spine clearance guideline led to increasing CT of C1 to C4 over full C-spine imaging, reducing the radiation dose in children. Level of Evidence: Level IV, therapeutic.